2017
DOI: 10.1111/ejn.13589
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of attention and visual function on gait impairment in Parkinson's disease: influence of task and turning

Abstract: Gait impairment is a core feature of Parkinson's disease (PD) which has been linked to cognitive and visual deficits, but interactions between these features are poorly understood. Monitoring saccades allows investigation of real-time cognitive and visual processes and their impact on gait when walking. This study explored: (i) saccade frequency when walking under different attentional manipulations of turning and dual-task; and (ii) direct and indirect relationships between saccades, gait impairment, vision a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 151 publications
(191 reference statements)
5
32
0
1
Order By: Relevance
“…The lack of correlation between UPDRS score with gaze position difference is comparable to what has been found in previous studies (MacAskill et al, 2012;Stuart, Galna, Delicato, Lord, & Rochester, 2017). In addition, no correlation was found between eye gaze position difference and saccade rates ( =0.07, p = 0.85) or between disease duration and saccade rate during pursuit ( =-ρ ρ 0.22, p = 0.54) or between disease duration and other eye movement characteristics ( =0.19 p = ρ 0.6 for pursuit gain; =-0.24, p = 0.51 for eye position difference).…”
Section: Figuresupporting
confidence: 90%
“…The lack of correlation between UPDRS score with gaze position difference is comparable to what has been found in previous studies (MacAskill et al, 2012;Stuart, Galna, Delicato, Lord, & Rochester, 2017). In addition, no correlation was found between eye gaze position difference and saccade rates ( =0.07, p = 0.85) or between disease duration and saccade rate during pursuit ( =-ρ ρ 0.22, p = 0.54) or between disease duration and other eye movement characteristics ( =0.19 p = ρ 0.6 for pursuit gain; =-0.24, p = 0.51 for eye position difference).…”
Section: Figuresupporting
confidence: 90%
“…The study involved a convenience sample of 55 people with PD and 32 age‐matched healthy older adult controls. Due to the exploratory nature of this study, there were no specific previous cueing examples available to guide sample‐size requirements; therefore, previous eye‐tracking during walking research was used to base our sample‐size on (Galna et al ., ; Stuart et al ., , ). The study adhered to the Declaration of Helsinki and was approved by the ‘ Newcastle and North Tyneside NHS Research Ethics Committee 1 ’ (Ref: 13/NE/0128).…”
Section: Methodsmentioning
confidence: 99%
“…Saccades, particularly saccade frequency, form the basis of visual exploration and are influenced by both visual and attentional neural processes (Kimmig et al ., ), which provides a means to examine the mechanisms underlying response to visual cues. Our recent work has shown that people with PD make significantly fewer saccades when walking than age‐matched older adults particularly under a dual‐task (Galna et al ., ), with attentional mechanisms underpinning saccadic and gait impairment in PD (Stuart et al ., ). A visual cue intervention may ameliorate deficits by prompting more frequent saccades, as recent studies have shown that cues increase visual exploration (fixation number) during gait in PD (Vitorio et al ., ; Beck et al ., ), but the underlying mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Individuals with PD are known to fixate on objects while turning which impedes anticipatory eye movements ahead of the turn, resulting in altered segment coordination during turning (Ambati et al, 2016;Stuart et al, 2017). This was evident, in the pre-trials of our study where anticipatory eye movements were not observed (Figure 1), and the resulting sequence of body reorientation occurred from the pelvis up (Figure 4).…”
Section: Pd Participantsmentioning
confidence: 72%